Mini volleyball games using plastic balls improve passing learning outcomes for grade IV elementary school - M. Zainudin; Destriani Destriani; Syafaruddin Syafaruddin (Lambung Mangkurat University, 2024)
This research aims to improve the learning outcomes of passing under volleyball using plastic balls for class VI students at 14 North Indralaya State Elementary School. This research is Classroom Action Research which consists of two cycles and each cycle consists of two meetings. This research took place at 14 North Indralaya State Elementary School. The subjects of this research were class VI students at 14 North Indralaya State Elementary School. The instrument in this research is to record students' psychomotor aspect scores during ongoing learning, and the results of students' performance in passing a volleyball with a plastic ball. Based on the results of observations, discussions and research results, it can be concluded that learning to pass down using a plastic ball in class VI students at 14 North Indralaya State Elementary School. Over two cycles it can improve student learning outcomes. This can be proven from the research results which show that the completeness of learning outcomes based on KKM, in the first cycle of students who completed it reached 58% and the average score was 58.62, then it increased in the second cycle of action, students who completed it reached 86% with an average score of the class average reached 86.20.